Contemporary Opinions on Intraoperative Facial Nerve Monitoring. Issue 3 (August 2018) - Gidley, Paul W.; Maw, Jennifer; Gantz, Bruce; Kaylie, David; Lambert, Paul; Malekzadeh, Sonya; Chandrasekhar, Sujana S.
Objective: To examine the current trend in intraoperative facial nerve monitoring (IOFNM) training, performance, and reimbursement by subspecialists. Study Design: Cross-sectional survey of the American Neurotology Society, American Otological Society, American Society of Pediatric Otolaryngology, and program directors of otolaryngology–head and neck surgery programs accredited by the Accreditation Council on Graduate Medical Education. Setting: American Academy of Otolaryngology–Head and Neck Surgery Intraoperative Nerve Monitoring Task Force. Subjects and Methods: The task force developed 2 surveys, which were implemented through Surveymonkey.com: (1) a 10-question survey sent to 1506 members of the societies listed to determine IOFNM practice and reimbursement patterns and (2) a 10-question survey sent to the 107 accredited US otolaryngology residency program directors to examine the state of resident training on facial nerve monitoring. Results: Response rates were 18% for practicing physicians and 15% for residency program directors. The majority agreed that IOFNM was indicated for most otologic and neurotologic procedures. In addition to facial nerve monitoring, facial nerve stimulation was used in complex skull base and temporal bone procedures. When queried about reimbursement by Medicare, only 4.4% of surgeons responded that they received reimbursement. Program directors indicated universal exposure of residents to IOFNM, with 61% of programs giving residents formal training. Conclusions: IOFNM is widely used among otologists and neurotologists in the United States. The majority of residents receive formal training, and all residents are exposed to the setup, use, monitoring, and troubleshooting of the device. Reimbursement for IOFNM is reported by a paucity of those surveyed.